Applying portfolio theory to benefit endangered amphibians in coastal wetlands threatened by climate change, high uncertainty, and significant investment risk - Eaton, Mitchell J.; Terando, Adam J.; Collazo, Jaime A. (Frontiers in Conservation Science, 2024)
The challenge of selecting strategies to adapt to climate change is complicated by the presence of irreducible uncertainties regarding future conditions. Decisions regarding long-term investments in conservation actions contain significant risk of failure due to these inherent uncertainties. To address this challenge, decision makers need an arsenal of tools to help guide spatial conservation strategies. Theory asserts that managing risks can be achieved by diversifying an investment portfolio to include assets that respond inversely to one another under a given set of conditions. We demonstrate an approach for formalizing the diversification of land parcels and conservation actions by using correlation structure to quantify the degree of risk for any proposed management investment. We illustrate a framework for identifying habitat refugia by integrating species distribution modeling, climate scenarios, and changes to critical habitat. Using the plains coqui (Eleutherodactylus juanariveroi), an endangered amphibian known from only three small wetland populations on Puerto Rico’s coastal plains, we evaluate the distribution of potential refugia under two model parameterizations and four sea-level rise scenarios. We apply portfolio theory using two distinct objective functions and eight budget levels to inform investment strategies for mitigating risk and increasing species persistence probability. Models project scenario-specific declines in coastal freshwater wetlands from 2% to nearly 30% and concurrent expansions of transitional marsh and estuarine open water. Conditional on the scenario, island-wide species distribution is predicted to contract by 25% to 90%. Optimal portfolios under a benefit maximization objective function emphasizes translocating frogs to existing protected areas rather than investing in the protection of new habitat. Alternatively, optimal strategies using the second objective function – a risk-benefit tradeoff framework – include significant investment to protect parcels for the purpose of reintroduction or translocation. These findings suggest that leveraging existing protected areas for species persistence, while less costly, may represent excessive risk and could diminish conservation benefits. Although our modeling includes numerous assumptions and simplifications, this framework provides useful inference for exploring resource dynamics and developing robust adaptation strategies using an approach that is generalizable to other conservation problems which are spatial or portfolio in nature and subject to unresolvable uncertainty.